Survey on the Industrial Logging Activities in the Businga Territory (Nord-Ubangi Province) in Democratic Republic of the Congo) - Koto-te-Nyiwa Ngbolua; Armand Endowa Doikasiye; Modeste Ndaba Modeawi; Ruphin Djolu Djoza; Amédée Gbatea Kundana; Colette Masengo Ashande; Clarisse Falanga Mawi; Ange Thijenira Loketo; Emmanuel Moke Lengbiye; Jonas Nagahuedi Mbongu Sodi; Muhammad Ridwan (Britain International for Academic Research (BIAR) Publisher, 2021)
The aim of this study was to investigate industrial logging in Businga Territory. The survey was carried out by means of a questionnaire addressed to 235 people including 150 men (64%) and 85 women (36%) between 31 and 100 years of age, on the basis of free and informed consent. It emerged from this study that 110 subjects out of the 235 (46.8%) were from SICOTRA company and its surroundings and 125 respondents (53.2%) belonged to from KKF company and its surroundings. Of the 235 people surveyed, only 104 (or 44.3%) were workers from two companies, the rest were heads of groups, capitas, local notables and those who had not worked in either company. 44.6% of the respondents had a primary level followed by 31.9% (or 75 people) with a secondary level. There are 55 illiterate people (23.4%). No university executives were met in the area during the survey. The logging by these two companies (KKF: from 1949 to 1998 (49 years of exploitation) and SICOTRA: from 1980 to 1998 (18 years)) has caused enormous destruction of the ecosystem and the population is today confronted with multiple difficulties and problems of supply of Non Timber Forest Products (caterpillars, snails, mushrooms, Cola acuminata, etc.) and the erosion of biodiversity. Of the 17 forest species exploited in this Sector, 03 have totally disappeared: Diospyros crassiflora Hiern, Nauclea diderrichii (De Wild.) Merr. and Prioria balsaminfera (Vermoesen) Breteler. The majority contacted had no notion of protecting the forest (67.2% vs. 32.8%); the population had no notion of drawing up specifications (95 vs. 5%). The results revealed that the indigenous population did not benefit from their forest, nor did they benefit from basic social infrastructures of community interest. In order to remedy this situation, a good regulation of the forestry exploitation code, the popularization of the new forestry code and the elaboration of specifications in collaboration with local communities are necessary to correct this situation in the future.